1995
DOI: 10.1021/es00010a015
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration of Polycyclic Aromatic Compounds from Sediments to Muscle of Finfish

Abstract: The uptake of polycyclic aromatic compounds (PAC) from contaminated sediments into the muscle of finfish is described and modeled. Winter flounder (Pseudopleuronectes americanus) were exposed to various concentrations of Hibernia crude oil in sediments during 4 months in the winter. Concentrations of parental and specific alkylated PAC, including polycyclic aromatic hydrocarbons (PAH) and a polycyclic aromatic sulfur heterocycle (PASH, represented by dibenzothiophene, DBT) were determined in sediments and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 34 publications
3
16
1
Order By: Relevance
“…This result for nitroaromatic compounds is in contrast with results obtained during studies of similar organic contaminants including PAHs, PCBs and other persistent organic pollutants, where it was reported that direct contact with sediment surfaces resulted in uptake by benthic fish (Stein et al, 1984;Hellou et al, 1994Hellou et al, , 1995Smith et al, 1996;Moermond et al, 2004;Fragoso et al, 2006). The body residue of benzo(a)pyrene via dermal contact, evaluated using anesthetized catfish (Ictalurus punctatus) placed directly on spiked sediment, was several times higher than in fish not in direct contact with the sediment (Smith et al 1996).…”
Section: Bioaccumulation and Toxicitycontrasting
confidence: 80%
See 1 more Smart Citation
“…This result for nitroaromatic compounds is in contrast with results obtained during studies of similar organic contaminants including PAHs, PCBs and other persistent organic pollutants, where it was reported that direct contact with sediment surfaces resulted in uptake by benthic fish (Stein et al, 1984;Hellou et al, 1994Hellou et al, , 1995Smith et al, 1996;Moermond et al, 2004;Fragoso et al, 2006). The body residue of benzo(a)pyrene via dermal contact, evaluated using anesthetized catfish (Ictalurus punctatus) placed directly on spiked sediment, was several times higher than in fish not in direct contact with the sediment (Smith et al 1996).…”
Section: Bioaccumulation and Toxicitycontrasting
confidence: 80%
“…Direct contact with sediment surfaces resulting in uptake of hydrophobic organic contaminants in benthic fish has been reported (e.g., Hellou et al, 1994Hellou et al, , 1995Smith et al, 1996) and therefore could be a potential route of exposure for explosive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation rates in sediments are typically slow, primarily due to the lack of oxygen required to initiate ring cleavage 14,18 . PAHs may also accumulate in fish 19 and edible shell-fish, thus their presence in seawater and sediments may constitute a chronic human health hazard. In general, fishes have a greater ability to metabolise PAHs than molluscs, so the compounds tend to persist more in the latter 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Some authors assume (incorrectly) that the uptake rate in the one compartment model is proportional to P ow , e.g., [28], rather than to ffiffiffiffiffiffiffiffi P ow p . This possibly originates from a wrong treatment of film models, where one-compartment models are used for film models on the assumption that the transport across the bi-film is in steady state 318 S. A. L. M. Kooijman et al and the concentration-jump at the interface between the two films equals the partition coefficient [29,30].…”
Section: Scaling Effects and Body Sizes 317mentioning
confidence: 99%